2016
DOI: 10.3390/cancers8120107
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Activation of TAM Family Receptors-Implications for Tumor Biology and Therapeutic Response

Abstract: The TAM family of receptors (i.e., Tyro3, Axl, and Mertk), and their ligands Growth arrest specific factor 6 (Gas6) and Protein S (Pros1) contribute to several oncogenic processes, such as cell survival, invasion, migration, chemo-resistance, and metastasis, whereby expression often correlates with poor clinical outcomes. In recent years, there has been great interest in the study of TAM receptors in cancer, stemming both from their roles as oncogenic signaling receptors, as well as their roles in tumor immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 105 publications
(110 reference statements)
1
54
0
1
Order By: Relevance
“…In some cases, MACS sorted splenic M-or G-MDSCs from B6 mice were added to the MLRs to determine their suppression of 2C T cell proliferation. ***P ≤ .001 approach actively tested in cancer therapies, 40 directly activating the kinase domain of MerTK is currently a concept that awaits the development of target-specific small molecule activators of this domain. Representative histograms were gated on 2C CD8 + T cells.…”
Section: Reciprocally We Tested Whether Graft Protection By Donor Ecmentioning
confidence: 99%
“…In some cases, MACS sorted splenic M-or G-MDSCs from B6 mice were added to the MLRs to determine their suppression of 2C T cell proliferation. ***P ≤ .001 approach actively tested in cancer therapies, 40 directly activating the kinase domain of MerTK is currently a concept that awaits the development of target-specific small molecule activators of this domain. Representative histograms were gated on 2C CD8 + T cells.…”
Section: Reciprocally We Tested Whether Graft Protection By Donor Ecmentioning
confidence: 99%
“…It is clear that, despite their common biological function, PS receptors are disparate in their structural arrangement and sequence homology across member. PS receptors often are regulated by different transcriptional and post‐translational mechanisms, and in many cases have unique expression patterns that add complexity to their biology …”
Section: Ps/ps‐receptor Interactions and The Regulation Of Efferocytomentioning
confidence: 99%
“…PS receptors often are regulated by different transcriptional and post-translational mechanisms, and in many cases have unique expression patterns that add complexity to their biology. 83 Finally, in addition to receptors or soluble proteins alluded to above that recognize PS when presented as an external signal, several scavenger receptors can broadly recognize the negative charge PS, adding both diversity and complexity to PS receptor signaling and function. 45 For example, CD36, CD91 (also called LDL-receptor related protein; LRP, the homolog of CED1) and CD68 have been implicated in the recognition and clearance of apoptotic cells, although as noted above, these receptors likely also recognize additional chemical modalities on the apoptotic cells, such as modified carbohydrates, acetylated components of the glycocalyx, and altered sialic acid residues (socalled apoptotic cell associated molecular patterns or ACAMPs).…”
Section: Ps/ps-receptor Interactions and The Regulation Of Efferocymentioning
confidence: 99%
“…This finding was followed by observational studies reporting 20–30% reductions in prostate cancer risk with VKA use as well as studies reporting neutral associations . In laboratory studies, VKAs have been demonstrated to inhibit Axl–receptor signaling involved in cell growth regulation and to reduce transcriptional activity of the androgen receptor in prostate cancer cells …”
Section: Introductionmentioning
confidence: 95%
“…[8][9][10] In laboratory studies, VKAs have been demonstrated to inhibit Axlreceptor signaling involved in cell growth regulation and to reduce transcriptional activity of the androgen receptor in prostate cancer cells. 11,12 Given the conflicting epidemiological findings and the potential implications for development of drugs for prevention or treatment of prostate cancer, we conducted a systematic review of the literature, examined the association between VKA use and prostate cancer risk in a nationwide nested case-control study, and pooled the risk estimates from previous and the present study in a meta-analysis.…”
Section: Introductionmentioning
confidence: 99%